Kejahatan Narkoba Sebagai Fenomena Dari Transnational Organized Crime - Zainab Ompu Jainah (PRANATA HUKUM, 2013)
Illicit drug trafficking undermine governance, institutions and societal cohesion. Drug traffickers typically seek the path where the rule of law is weak. In turn, drug-related crime deepens vulnerability to instability and poverty. In the period of the past two decades, Indonesia has become one of the countries that serve major markets from narcotics syndicate of international dimension for commercial purposes. For drug trafficking network in Asian countries, Indonesia is considered as the market (market- state) is the most prospective commercial for the International syndicates operating in developing countries.